2010
DOI: 10.1248/cpb.58.922
|View full text |Cite
|
Sign up to set email alerts
|

Latent Enamine Functionality of 5-Methyl-2,3-dihydropyrazines

Abstract: Dihydropyrazine derivatives (DHPs) derived from dimerization of amino sugars, such as glucosamine and mannosamine, spontaneously generate carbon-centered radicals and exhibit DNA strand-breaking activity, which may be related to the apoptotic activity of amino sugars.1,2) The DHP derivative 3,6-dihydropyrazine-2,5-dipropionic acid is formed by dimerization of 5-aminolevulic acid, which is accumulated in congenital and acquired hepatic porphyrias, such as acute intermittent porphyria, and might induce hepatocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…1). The highly reactive nature of the exo-methylene group of DHP has been attributed to its latent enamine functionality, and this result has been confirmed both experimentally and theoretically (Ito et al, 2010). The low energy distribution of the highest occupied molecular orbital (HOMO) on the exo-methylene group of the DHP moiety would allow it undergo nucleophilic addition reactions with various biological thiols, including cysteine and GSH.…”
Section: Resultsmentioning
confidence: 79%
“…1). The highly reactive nature of the exo-methylene group of DHP has been attributed to its latent enamine functionality, and this result has been confirmed both experimentally and theoretically (Ito et al, 2010). The low energy distribution of the highest occupied molecular orbital (HOMO) on the exo-methylene group of the DHP moiety would allow it undergo nucleophilic addition reactions with various biological thiols, including cysteine and GSH.…”
Section: Resultsmentioning
confidence: 79%
“…Finally, DHP tautomerizes and undergoes nucleophilic addition to acetaldehyde to synthesize EDMP. Other research groups reported that the DHP is easily oxidized under mild condition to form 2,5-dimethylpyrazine (DMP) 33 , 34 , suggesting that immediate reaction of DHP with acetaldehyde increases the production of EDMP. To confirm this point, we compared production rates of EDMP and DMP by changing the timing of acetaldehyde addition (Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pyrazine scaffold is one of the privileged azaheterocyclic structural motifs in many natural products [44] and synthetic compounds [45] with biological activities, as well as in functional materials [46]. 2,3-Dihydropyrazines, which are direct precursors of pyrazines, are known to have an important role as flavorants [47] and are assumed to actively participate in DNA strand cleavage [48][49][50] and cyclooxygenase inhibition [51]. In addition, the pyrazine derivatives can efficiently act as ligands in the construction of metallosupramolecular architectures because of their two N-coordinating sites [52][53][54][55][56][57], as well as building blocks in the design of photoluminescence devices [46].…”
Section: Introductionmentioning
confidence: 99%